Analisis Faktor-Faktor yang mempengaruhi Ketepatwaktuan Penyampaian Laporan Keuangan - Jihan Putri Kusuma Makki (CV. Syntax Corporation Indonesia, 2022)
At the end of every year, all companies, both listed on the Indonesia Stock Exchange (IDX) and unlisted, will issue financial reports. Submission of financial statements aims to provide information about the total assets, debts, and sales and ongoing operating expenses in the company. The purpose of this study is to test the timeliness of the financial statements of the technical sector. Timeliness in this study uses a dummy variable. The data used in this study came from financial statement data. The population in this study are technology companies listed on the IDX. The sample selection technique used was purposive sampling and obtained 20 companies for the 2016-2020 research period. The data analysis method of this research is logistic regression analysis using SPSS 26 software. The results show that partially liquidity, leverage ratio and company size have a significant positive effect on the timeliness of financial report submission. The variables of profitability, reputation of the public accounting firm and auditor's opinion have no significant effect on the timely submission of financial statements.